Power Sector Under Climate Scenario: A Study of Climate Policy Impact on Indonesia Electricity System - Kurniawan, Hendra; Iskandar, Iskhaq; Sidik, Muhammad Abu Bakar (Indonesian Journal of Environmental Management and Sustainability, 2024)
In the sixth assessment report, the IPCC indicates that global temperature increased by 1.11 (±0.13) degrees Celsius in 2019 due to 6.5 gigatons of CO2eq of greenhouse gas emissions into the atmosphere. The power sector is a major global greenhouse gas emitter, particularly in Indonesia. Indonesia’s electricity sector emitted 149.90 million tons of CO2eq greenhouse gas in 2020, which is expected to increase to 158.30 million tons of CO2eq in 2021. Indonesia has committed to reducing greenhouse gas emissions according to the Paris Agreement. The Paris Agreement has been ratified into national law, accommodating Indonesia’s roadmap to net zero by 2060. The emissions reduction target was published in 2022 through the enhanced Nationally Determined Contribution (NDC). This study aims to analyze the impact of climate policy in Indonesia’s electricity sector to meet the net zero emissions target by 2060. Projection and calculation in this study were conducted using the Low Emissions Analysis Platform (LEAP). Data from 2020, including electricity demand, existing capacity, energy production, energy intensity, lifetime, and capacity factor, were used to support LEAP analysis. The data were obtained from the PLN statistical book, PLN sustainability report, Indonesia’s statistical book, and climate change mitigation and adaptation reports in Indonesia. This study developed three climate scenarios, including business as usual (BAU), sustainable development (SD), and low-carbon development (LCD). These scenarios draw upon current climate policies that have various impacts on electricity generation in Indonesia. Based on LEAP analysis, by 2060, energy demand is expected to increase to 300.36 MTOE (BAU), 200.93 MTOE (SD), and 76.97 MTOE (LCD). Consequently, each climate scenario requires an increase in installed capacity to 821.82 GW (BAU), 727.06 GW (SD), and 334.58 GW (LCD). The renewable energy mix is projected to be 21% (BAU), 69% (SD), and 100% (LCD). Each scenario requires investment to develop capacity to meet energy demand. The investment cost is estimated to be 1,671.58 million USD (BAU), 1,537.64 million USD (SD), and 816.51 million USD (LCD). GHG emissions are projected to rise to 1,746.31 million tons of CO2eq (BAU) and 264.39 million tons of CO2eq (SD). However, the LCD scenario expects to achieve net zero emissions by 2060.